Les cours d’eau dans les incantations chamaniques des Indiens yucuna (Amazonie colombienne) - Laurent Fontaine (Journal de la Société des Américanistes)
Rivers in shamanic incantations of Yucuna Indians (Colombian Amazon). For Yucuna Indians, every river has its history, its masters or original inhabitants. They are mentioned in invocations called juní maná (« invocations of water »). These invocations are one of fundamentals of the shamanism of the Yucuna : they constitute a basic structure repeated in many incantations, which are supplemented with other invocations depending on the type of treatment to be provided. They recall, explain and situate the origin of every natural element referring to some particular extract of history or myth, considered with its consequences in everyday life. In this text, the « invocations of water » are presented in their original language with the comments of the therapist.